Embryonic motor activity and implications for regulating motoneuron axonal pathfinding in zebrafish - Menelaou, Evdokia (Blackwell Publishing Ltd, 2008)
Zebrafish embryos exhibit spontaneous contractions of the musculature as early as 18–19 h post fertilization (hpf) when removed from their protective chorion. These movements are likely initiated by early embryonic central nervous system activity. We have made the observation that narrowminded mutant embryos (hereafter, nrd(−/−)) lack normal embryonic motor output upon dechorionation. However, these mutants can swim and respond to tactile stimulation by larval stages of development. nrd(−/−) embryos exhibit defects in neural crest development, slow muscle development and also lack spinal mechanosensory neurons known as Rohon–Beard (RB) neurons. At early developmental stages (i.e. 21–22 hpf) and while still in their chorions, nrd siblings (nrd(+/?)) exhibited contractions of the musculature at a rate similar to wild-type embryos. Anatomical analysis indicated that RB neurons were present in the motile embryos, but absent in the non-motile embryos, indicating that the non-motile embryos were nrd(−/−) embryos. Further anatomical analysis of nrd(−/−) embryos revealed errors in motoneuron axonal pathfinding that persisted into the larval stage of development. These errors were reversed when nrd(−/−) embryos were raised in high [K(+)] beginning at 21 hpf, indicating that the abnormal axonal phenotypes may be related to a lack of depolarizing activity early in development. When activity was blocked with tricaine in wild-type embryos, motoneuron phenotypes were similar to the motoneuron phenotypes in nrd(−/−) embryos. These results implicate early embryonic activity in conjunction with other factors as necessary for normal motoneuron development.